Kinerja Wirausahawati Umkm Diy Berbasis Orientasi Kewirausahaan Di Masa Pandemi Covid-19 - Sofiati Sofiati (Universitas Hamzanwadi, 2020)
Women are increasingly having an important role in improving the country’s economy through the umkm sector. The condition of the Covid-19 pandemic could have an impact on decreasing the performance of women workers or vice versa, in fact there wasan increase in oerformance in several umkm as a result of proactive,innovative behavior and courage in taking risks from entrepreneurs.this study aims to analyze the factors that influence the performance of self-employed entrepreneurs based on the entrepreneurship orientation of umkm diy. This study uses a causal quantitative deisgn.data source based on survey.technique sampling using random sampling of 100.method of data analysis using multiple regression analysis.the results showed that simultaneously the entrepreneurial orientation of women entrepreneurs consisting of factors of proactiveness, innovativeness, and risk taking to significantly affect the performance of umkmdiy entrepreneurs during the covid19 pandemic. However, partially risk taking entrepreneurial orentation factors are not proven to significantly affect the performance of umkm diy entrepreneurs during the covid 19 pandemic.the conclusion of the study shows that the performance of umkm female entrepreneurs during the pandemic covid19 based on entrepreneurrial orientation is proven to be significant except for the risk taking.this insignificance is due to different types of business so that the level of risk and risk taking preference will be different.